Pemaknaan Generasi Z Kota Medan Terhadap Fenomena Call Out Culture di Instagram - Pane, Endi Hadian Shabar; Rozi, Fakhrur (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Social media consistently generates intriguing phenomena worthy of discussion. One particularly widespread but seldom-studied phenomenon is Call Out Culture. Call Out Culture involves individuals or groups expressing their frustration and disappointment with specific events by calling out or satirizing those they perceive as responsible through social media platforms. This research aims to explore how Generation Z in Medan City interprets the phenomenon of Call Out Culture on Instagram. The study employs a descriptive qualitative method utilizing a snowball sampling technique, where the initially identified informant assists in recruiting subsequent participants. Data were collected through in-depth interviews and content analysis of relevant Instagram posts. The findings indicate that Generation Z in Medan City views Call Out Culture on Instagram as a means to advocate for social change and increase awareness of critical issues such as social injustice, human rights, and environmental concerns. However, they also recognize the necessity of a balanced approach in delivering criticism to avoid exacerbating conflicts. Generation Z demonstrated an awareness of the potential negative impacts of Call Out Culture, such as cyberbullying and social polarization, and stressed the importance of responsible use of social media as a tool for advocacy.